Influência do rejeito de mineração de nióbio na durabilidade de matrizes cimentícias - Filipe Siqueira Mazzaro (2022)
The operation and processing of ores is one of the main productive activities in Brazil. However, this sector can cause several environmental impacts, such as air pollution, contamination of the water table, suppression of vegetation, soil and relief degradation and damage to fauna and flora. In this context, niobium mining has a prominent position in the country, since more than 90% of the world production is in Brazilian deposits. The residues from this processing (from the magnetic separation, desliming and flotation steps) are disposed of in tailings dams, but may have potential application in construction materials. Therefore, the objective of this study is to evaluate the durability of cement matrices with niobium mining tailings in partial replacement of filler material and conventional fine aggregate. The materials were chemically and physically characterized, verifying that the tailings samples are rich in barite and magnetite/hematite, with a high content of fines and a high specific mass. The incorporation of the tailings occurred in substitutions referring to 25, 50 and 75% (in volume) of filler and natural sand in cementitious mortars. The physical-mechanical properties were analyzed, as well as the durability parameters, such as carbonation, pH of the pore solution, chloride penetration, electrical conductivity of the pore solution, electrical resistivity, resistance to high temperatures and radiation attenuation. The physical-mechanical results point to a good performance of the mortars with tailings, especially at levels close to 50%. The composites with tailings in contents above 25% showed potential application in heavy concrete structures. Electrical resistivity was reduced when incorporating tailings due to the high electrical conductivity of magnetite/hematite. Similar behavior between carbonation depth and porosity indicated an optimal content between 25% and 50% of tailings. The penetration of chlorides showed a slight increase in the levels of 50% and 75% of tailings. At high temperatures, the tailings showed good thermal stability and low water absorption capacity. As for radiation attenuation, the samples showed similar performance in relation to the linear attenuation coefficient and the semi-reducing layer, in addition to good performance in the 50% and 75% contents about the mass attenuation coefficient. Therefore, the results indicate good performance in the physical-mechanical and durability tests at levels with approximately 50% replacement by tailings, indicating an eco-efficient alternative for tailings from niobium mining.